The effect of 8 weeks aerobic exercise training on cardiovascular risk factors in men with type 2 diabetes mellitus - Seyyed Zoheir Rabei; Mohsen Salesi (Islamic Azad University, 2015)
Introduction: Individuals with diabetes are often diagnosed with low high-density lipoprotein cholesterol (HDL-C) concentration, hypertriglyceridemia and development of cardiovascular disease (CVD). The purpose of this study was to determine the impact of aerobic training on blood profile and inflammatory marker (CRP) of type 2 diabetes mellitus (T2DM) people. Methods: Thirty diabetic males were recruited (age: 50.34 ± 10.28 years) and randomly assigned to 8 weeks aerobic exercise training (n = 15) and control groups (n = 15). Before and after training blood pressure, weight, lipid profile (Total cholesterol [TC], triglyceride [TG], low-density lipoprotein cholesterol (LDL-C), HDL-C) and high-sensitivity C-reactive protein (hs-CRP) were measured. Exercise training was in mode of walking and consisted of 5 exercise sessions/week at 50%-70% heart rate maximum and began with 25 minutes of walking. Training increased each week by 5 minutes until 60 minutes of walking was reached. Each exercise session included approximately 10 minutes of warm-up and cool-down periods. Results: Resting systolic blood pressure decreased following 8 weeks of aerobic training (pre 139 ± 16 vs post 121 ± 11 mm Hg, P = 0.04). Also, TG significantly decreased (pre 210.19 ± 9.31 vs 191.12 ± 7.25, P = 0.03) and HDL-C significantly increased (pre 42.37 ± 3.15 vs 47.56 ± 2.19, P = 0.01) after exercise training. However, there was no difference between groups in TC, LDL-C, body mass index (BMI) and weight. In addition, a decrease in fasting blood glucose levels showed a significant difference between groups (pre 142.43 ± 7.96 vs 121.17 ± 8.32, P = 0.04). Conclusion: Regular aerobic exercise training can improve the lipid profile and reduce the cardiovascular risk factors in T2DM patients. Exercise, like walking, is inexpensive and has relatively few negative side effects when performed properly.